Overview of residual cardiovascular risk - Aristizabal, David; Quintero-Zea, Karina; Sierra-Castillo, Santiago (Interdisciplinary Journal of Epidemiology and Public Health, 2024)
Cardiovascular risk is an entity that constantly climbs ranks in the Global Burden of Disease as an agent associated with morbidity and mortality.As of today, there are guidelines that guide the management of cardiovascular risk for the prevention of associated diseases, however, once the proposed goals for risk reduction have been achieved, unwanted clinical outcomes persist, associated with the called Residual Cardiovascular Risk.Some agents such as obesity, fatty liver, triglycerides, inflammation, thrombotic risk and metabolic risk, have been targeted for research and strengthening in order to reduce the occurrence of cardiovascular events once the proposed cardiovascular risk goals have been achieved. by international guidelines.Currently there are some strategies such as the use of Colchicine, Rivaroxaban, Ethyl Eicosapent, PCSK9 inhibitors, among others, have shown favorable clinical outcomes associated with the reduction of residual cardiovascular risk.